1989
DOI: 10.1029/ja094ia02p01303
|View full text |Cite
|
Sign up to set email alerts
|

Steady state magnetic field configurations for the Earth's magnetotail

Abstract: We present a two‐dimensional, force‐balanced magnetic field model in which flux tubes have constant pVγ throughout an extended region of the nightside plasma sheet, between approximately 36 RE geocentric distance and the region of the inner edge of the plasma sheet. We have thus demonstrated the theoretical existence of a steady state magnetic field configuration that is force‐balanced and also consistent with slow, lossless, adiabatic, earthward convection within the limit of the ideal MHD (isotropic pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 40 publications
2
77
1
Order By: Relevance
“…This relation is valid in the MHD tail approximation when magnetic tension f Árf is negligible. Indeed, solutions of the Grad-Shafranov equation for stationary magnetospheric con®gurations with a MFM lead to quite dierent radial pressure pro®les (see, for example, Hau et al, 1989). However, there are several aspects of the magnetospheric neutral sheet structure in the``wall region'' that are not taken into account in the static Grad-Shafranov equation.…”
Section: A2mentioning
confidence: 99%
See 2 more Smart Citations
“…This relation is valid in the MHD tail approximation when magnetic tension f Árf is negligible. Indeed, solutions of the Grad-Shafranov equation for stationary magnetospheric con®gurations with a MFM lead to quite dierent radial pressure pro®les (see, for example, Hau et al, 1989). However, there are several aspects of the magnetospheric neutral sheet structure in the``wall region'' that are not taken into account in the static Grad-Shafranov equation.…”
Section: A2mentioning
confidence: 99%
“…Evidently, for the isotropic pressure case, a more rigorous treatment is possible, in comparison with that in GVZ92, of the magnetic ®eld structure in equilibrium with plasma pressure with the use of magnetic vectorpotential A(r 0 ,z) and Grad-Shafranov equation. Its solution, with the given B Z (r 0 ) as a boundary condition, can be sought in a way described in Hau et al (1989), andHau (1991). For an adiabatic lossless convection, Hau et al (1989) show that to avoid the``pressure balance inconsistency'', a minimum must appear in the magnetic ®eld B Z (r 0 ) pro®le.…”
Section: Comparisons With the Gvz92 Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Steady magnetospheric convection, as the name implies, has been explained in terms of convection in the plasma sheet [Hau et al, 1989], but to our knowledge, the deep minimum in the tail magnetic field required by this explanation has not been found. IN Figure 2d for R4.…”
Section: Unloading Event Figure 3 Gives Another Representation Of Onmentioning
confidence: 99%
“…Since such pressures are not observed, it was concluded that sunward convection must be an unsteady process. Later, Hau et al [1989] and Hau [1991] constructed a steady force-balanced MHD model in which the magnetotail has a broad minimum in the equatorial magnetic field strength in the near-Earth plasma sheet. In such a model, steady convection becomes possible.…”
Section: Introductionmentioning
confidence: 99%